Análisis situacional de la Isla Santay del cantón Duran para el desarrollo del turismo ecológico - Reasco Muñoz, Jean Paul (2021)
This case study refers to the city of Duran Isla Santay, situational analysis of the Santay Island of the Duran Canton for the Development of Ecological Tourism, being a protected area recognized by the MAE and SNAP of the province of Guayas (Humedal del Santay), is well known for its ecological houses (Ecovillage) and its way of generating electricity through solar panels. This island is located in the Guayas river between the city of Duran and Guayaquil Through observation we were able to realize the problems that the bridge has on the Duran side that hinders the tourist influx and also due to the lack of knowledge of residents about Santay Island and its tourist attractions that it has, such as its world-renowned Wetland.